The Kishinev Ghetto, 1941-1942 : A Documentary History of the Holocaust in Romania's Contested Borderlands - Shapiro, Paul A. (Book collections on Project MUSE., 2015)
"The Kishinev Ghetto, 1941-1942 sheds new light on the little-known historical events surrounding the creation, administration, and liquidation of the Kishinev (Chisinau) ghetto during the first months following the Axis attack on the Soviet Union (Operation Barbarossa) in late June 1941. Mass killings during the combined Romanian-German drive toward Kishinev in Bessarabia, after a year of Soviet rule in this Romanian border province, were followed by the shooting of thousands of Jews on the streets of the city during the first days of reestablished Romanian administration. Survivors were driven into a ghetto, persecuted, and liquidated by year's end. The Kishinev Ghetto, 1941-1942 is the first major study of these events. Often overshadowed by events in Germany and Poland, the history of the Holocaust in Romania, including what took place in Bessarabia (corresponding in large part with the territory of the modern Republic of Moldova), was obscured during decades of communist rule, denial, and policies that blocked access to wartime documentation. This book is the result of a lengthy research project that began with Paul A. Shapiro's travels to Romania for the United States Holocaust Memorial Museum to negotiate access to these documents."--